The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1038/srep08698
|View full text |Cite
|
Sign up to set email alerts
|

Performance comparison of LUR and OK in PM2.5 concentration mapping: a multidimensional perspective

Abstract: Methods of Land Use Regression (LUR) modeling and Ordinary Kriging (OK) interpolation have been widely used to offset the shortcomings of PM2.5 data observed at sparse monitoring sites. However, traditional point-based performance evaluation strategy for these methods remains stagnant, which could cause unreasonable mapping results. To address this challenge, this study employs ‘information entropy’, an area-based statistic, along with traditional point-based statistics (e.g. error rate, RMSE) to evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 41 publications
0
45
1
Order By: Relevance
“…Generally, the accuracy of the PM 2.5 concentrations was computed using the self-adaptive LUR model and was higher than the typical LUR model. In addition, the accuracy of the typical LUR model evaluated using LOO cross validation (result before Kriging interpolation) was less than the final map accuracy, which verified that Kriging improves the accuracy of the LUR model [50].…”
Section: Comparison With the Typical Lur Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…Generally, the accuracy of the PM 2.5 concentrations was computed using the self-adaptive LUR model and was higher than the typical LUR model. In addition, the accuracy of the typical LUR model evaluated using LOO cross validation (result before Kriging interpolation) was less than the final map accuracy, which verified that Kriging improves the accuracy of the LUR model [50].…”
Section: Comparison With the Typical Lur Methodsmentioning
confidence: 85%
“…Finally, the choice of the spatial interpolation method is critical. Most studies have found that the final pollutant concentration distribution map is more accurate when combined with the Kriging interpolation method [50].…”
Section: Self-adaptive Revised Lur Modelmentioning
confidence: 99%
“…In this process, the meteorological parameters with ground-based measurements were spatially interpolated to the fine grid of 10 km, which corresponds to the grid resolution of AOD datasets. For predictors with spatial scaling effects (e.g., land use/cover), the characteristic values were extracted at a 500-5000 m buffering radius based on previous findings [35,36]. Finally, PM 2.5 , fused AOD, meteorological parameters, pollution sources, road network, land use/cover, terrain, and population for all PM 2.5 monitoring sites were matched by PM 2.5 monitoring site IDs for model development.…”
Section: Data Integrationmentioning
confidence: 99%
“…In one method, the particle concentrations of the stations are obtained based on the constructed model, and the simulation of the spatial distribution of the PM 2.5 concentration is achieved through spatial interpolation [18,19]. In the other method, the raster data of variables are incorporated into the model for regression analysis mapping to obtain the spatial distribution of the PM 2.5 concentration [20].…”
Section: Introductionmentioning
confidence: 99%